2005
DOI: 10.1213/01.ane.0000143566.60213.0a
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Intraabdominally Insufflated Carbon Dioxide on Hepatic Blood Flow During Laparoscopic Surgery Assessed by Transesophageal Echocardiography

Abstract: Conflicting results have been published about the effects of carbon dioxide (CO(2)) pneumoperitoneum on splanchnic and liver perfusion. Several experimental studies described a pressure-related reduction in hepatic blood flow, whereas other investigators reported an increase as long as the intraabdominal pressure (IAP) remained less than 16 mm Hg. Our goal in the present study was to investigate the effects of insufflated CO(2) on hepatic blood flow during laparoscopic surgery in healthy adults. Blood flow in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 28 publications
0
29
0
1
Order By: Relevance
“…Laparoscopic cholecystectomy using low-pressure pneumoperitoneum (7 mmHg) also has been shown to minimize adverse hemodynamic effects on hepatic portal blood flow and hepatic function [25]. Meierhenrich et al [13] reported well-preserved, even increased, hepatic blood flow during laparoscopic cholecystectomy (LCC) measured with advanced transesophageal echocardiography [13]. In our study, we observed no adverse effects on hepatic function, as measured by laboratory parameters, or on liver perfusion, as measured with indocyanin clearance, when IAP was kept between 8 and 12 mmHg.…”
Section: Discussionmentioning
confidence: 99%
“…Laparoscopic cholecystectomy using low-pressure pneumoperitoneum (7 mmHg) also has been shown to minimize adverse hemodynamic effects on hepatic portal blood flow and hepatic function [25]. Meierhenrich et al [13] reported well-preserved, even increased, hepatic blood flow during laparoscopic cholecystectomy (LCC) measured with advanced transesophageal echocardiography [13]. In our study, we observed no adverse effects on hepatic function, as measured by laboratory parameters, or on liver perfusion, as measured with indocyanin clearance, when IAP was kept between 8 and 12 mmHg.…”
Section: Discussionmentioning
confidence: 99%
“…15,16) Hypotension due to decreased systemic vascular resistance may reduce hepatic blood flow, because a nearly linear correlation between systemic arterial blood pressure and hepatic arterial blood flow has been found. 17,18) In previous studies, hepatic blood flow has been measured using intraoperative transesophageal echocardiography to investigate the effect of laparoscopic cholecystectomy, 19) intraabdominally insufflated carbon dioxide, 20) and thoracic epidural anesthesia. 21) In these studies, hepatic blood flow was reported to be decreased by laparoscopy and thoracic epidural anesthesia, and increased by insufflated carbon dioxide.…”
Section: Influence Of Hemodynamic Variations On the Pharmacokinetics mentioning
confidence: 99%
“…19,20,[24][25][26] To visualize the hepatic veins, the tip of the probe was advanced into the antrum of the stomach and flexed anteriorly. The Doppler sonography curve was attained by pulsed wave Doppler technique (PWmode).…”
Section: Assessment Of Hepatic Blood Flowmentioning
confidence: 99%
See 2 more Smart Citations